THE POTENTIAL CORRELATION BETWEEN HYPERURICEMIA AND HYPERTHYROIDISM IS BEING EXAMINED - KHAN, AM; KHAN, Z; BASIT, A; KHAN, MA; ALI, A (Biological and Clinical Sciences Research Journal, 2023)
Hyperuricemia is characterized by high levels of uric acid in the bloodstream, while hyperthyroidism refers to excessive thyroid gland activity. Both conditions can significantly affect a patient's quality of life. This study aimed to comprehensively analyze a sample size of 100 patients at MTI LRH, Peshawar, to address the research gap in this area. The study employed a prospective design, which involved collecting patient data over time. The study was conducted at the Department of Medicine, Medical Teaching Institution Lady Reading Hospital (MTI LRH), Peshawar, from January to July 2021. One hundred patients were chosen randomly from those who presented at MTI LRH during the study period. The inclusion criteria were individuals 18 or older who had documented thyroid function test results and had blood uric acid levels on record. The study participants included 50 males and 50 females, with a median age of 41. Most participants (55%) were between the ages of 31 and 50, with 25% in the 31-40 age group and 30% in the 41-50 age group. The remaining 45% were younger than 30 or older than 50. The data showed a slight negative correlation (r = -0.15) between TSH and uric acid levels, indicating that as TSH levels decreased, uric acid levels increased. However, this correlation was not statistically significant (p=0.20). The study found no significant correlation between thyroid function and uric acid levels in the sample population. Although there have been inconsistencies in previous literature on this topic, our results were consistent with past investigations.